1995
DOI: 10.1002/art.1790080207
|View full text |Cite
|
Sign up to set email alerts
|

Concordant and discrepant views of patients' physical functioning

Abstract: Objective. Although considerable research has been done on patient-physician interaction, few studies have examined discrepancies between patients and physicians in their assessments of the patient's physical functioning. One recent study reports such discrepancies between rheumatologists and 41 % of their rheumatoid arthritis patients. This article reports data replicating that study and examining the relationships between such discrepancies and a number of other variables.Methods. This is a longitudinal stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 16 publications
3
48
0
3
Order By: Relevance
“…Observational studies are best suited to address these aspects and take into account a diversity of relevant outcomes not considered in short-term trials. Depression has been consistently associated with worse disease outcomes in patients with RA, including pain, tender joints, poor adherence to medication, increased healthcare service utilization, disability, and higher rates of early retirement [2,5,[39][40][41][42]. Conversely, several studies have demonstrated that functional disability and loss of valued activities, such as employment, are associated with an increased risk of depression [39,42,43].…”
Section: C Psychological Factors Influencing the Effectiveness Of mentioning
confidence: 99%
“…Observational studies are best suited to address these aspects and take into account a diversity of relevant outcomes not considered in short-term trials. Depression has been consistently associated with worse disease outcomes in patients with RA, including pain, tender joints, poor adherence to medication, increased healthcare service utilization, disability, and higher rates of early retirement [2,5,[39][40][41][42]. Conversely, several studies have demonstrated that functional disability and loss of valued activities, such as employment, are associated with an increased risk of depression [39,42,43].…”
Section: C Psychological Factors Influencing the Effectiveness Of mentioning
confidence: 99%
“…8,15 The correlation of objective measures of pathophysiology (eg, stiffness, arthritis, injury severity) 9 with patient-reported outcome measures is consistently much less than the correlation with psychosocial factors. 1,3,4,[10][11][12]18,22,23 These findings are important given the increasing emphasis on value and patient-reported outcome measures. All hand-and upper extremity-related patient-reported outcome measures studied to data are strongly influenced by psychological and sociological factors.…”
Section: Discussionmentioning
confidence: 99%
“…The Abbreviated PCS is a validated short form of the PCS that utilizes 4 questions (items 3,6,8,11) to assess coping strategies in response to nociception. 4 The maximum score is 16, with a higher score indicating a higher level of catastrophic thinking.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…(10)(11)(12) In many cases, however, what we as providers consider substantial improvement does not align with the perceptions and experiences of our patients. (13,14) That is not to say that traditional objective metrics cannot show significant differences in outcomes; rather, what is measured by these functional tests often does not translate to the outcomes desired by the patient, provider, or society. For example, fracture union on x-ray does not equate with a patient having high satisfaction with their outcome or with returning to activities of daily living (ADL).…”
Section: Patient-reported Outcomes In Hand Surgerymentioning
confidence: 99%